The educational curriculum in the Holy Quran and the Noble Sunnah - raising a child for example - Mohammed Morteza Mohammed Ali Al-Muzaffar ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The Noble Qur’an is the word of God Almighty, and it is the first weight that the Messenger of God Muhammad bin Abdullah brought. To bring people out of the darkness to the light and guide them to the straight path, so he left it to all the people and the Islamic community in particular, as he left among them the people of his house - shining with their light, and one of them is complementary to the other - for they are not separated until they are returned and we will return with them two witnesses to us and we will bear witness to them on the Day of Resurrection in the hands of the Messenger of God and the pure people of his household. The Islamic educational curriculum is derived from it, and the curriculum of the Prophet and the pure people of his household is a Quranic educational curriculum, so God Almighty has delegated them to educate the ummah according to this curriculum. So, he (may God’s prayers and peace be upon them all) explain it to the people and the Islamic community to achieve the goals of doctrinal education, moral education, physical education, mental education, psychological education, social education, and sexual education. This brief research was nothing but a serious attempt to show some examples of an infallible educational approach for the Islamic nation, including raising the child within his community and his homeland. In order for the research to achieve some of the desired educational goals.